New Physical and Mathematical Model of Radiation Heat Transmission Inside Circular Furnace - V. I. Timoshpolsky; M. L. German; D. N. Andrianov; I. A. Trusova; S. M. Kabishov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Methods of solving problems concerning heat transmission by radiation are considered in the paper. The paper shows disadvantages of the existing techniques. A physical and mathematical model of a conjugate heat exchange has been developed to eliminate the above disadvantages.